2015
DOI: 10.2196/jmir.3992
|View full text |Cite
|
Sign up to set email alerts
|

eHealth Literacy and Web 2.0 Health Information Seeking Behaviors Among Baby Boomers and Older Adults

Abstract: BackgroundBaby boomers and older adults, a subset of the population at high risk for chronic disease, social isolation, and poor health outcomes, are increasingly utilizing the Internet and social media (Web 2.0) to locate and evaluate health information. However, among these older populations, little is known about what factors influence their eHealth literacy and use of Web 2.0 for health information.ObjectiveThe intent of the study was to explore the extent to which sociodemographic, social determinants, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

60
453
6
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 621 publications
(561 citation statements)
references
References 55 publications
60
453
6
11
Order By: Relevance
“…Several studies showed that the information on this platform was not regulated and contains both high-and low-quality health information. This resulted in misinformation or disinformation for individuals seeking online healthcare information [37][38][39][40][41][42][43].…”
Section: Medical Informationmentioning
confidence: 99%
“…Several studies showed that the information on this platform was not regulated and contains both high-and low-quality health information. This resulted in misinformation or disinformation for individuals seeking online healthcare information [37][38][39][40][41][42][43].…”
Section: Medical Informationmentioning
confidence: 99%
“…In particular, literacy level and computer access among target populations, such as older adults, were issues that hindered implementation. Although, computer access is becoming less of an issue as older adults and agencies serving older adults are increasingly using technology [50]. Another consistent challenge reported across both programs was the time commitment for health educators.…”
Section: Discussionmentioning
confidence: 99%
“…Chan and Kaufman also found barriers related to evaluating the trustworthiness and credibility of health information [11,19,20]. On the other hand, the skills associated with media literacy, especially in the context of new media / social media is not well understood [21][22][23]. Science literacy as it pertains to matters of health, has been an area of inquiry in educational research for some time [24].…”
Section: Barriers To Effective Functioning In the World Of Digital Ehmentioning
confidence: 99%